2021
DOI: 10.1155/2021/6929971
|View full text |Cite|
|
Sign up to set email alerts
|

Impact of HSP90α, CEA, NSE, SCC, and CYFRA21-1 on Lung Cancer Patients

Abstract: Lung cancer is a lethal disease, and early diagnosis with the aid of biomarkers such as HSP90α protein can certainly assist the doctors to start treatment of patient at the earliest and can save their lives. To analyse the diagnostic value of HSP90α expression in lung cancer patients by collecting data of patients through IoT devices to avoid delay in treatments, a study has been presented in this paper where the significance of HSP90α biomarker is highlighted in early diagnosis of patients suffering from lung… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…Previous studies showed that plasma Hsp90 levels are positively correlated with tumor malignancy, which may be a potential clinical diagnostic and prognostic marker ( Wang et al, 2009 ). Moreover, extracellular HSP90α has recently been tested as an excellent biomarker for liver and lung cancer in clinical practices ( Fu et al, 2017 ; Zhou et al, 2021 ). According to recent demonstrations, the area under the diagnosis curve of eHSP90α against lung cancers appears to be 0.857, with outstanding sensitivity and specificity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies showed that plasma Hsp90 levels are positively correlated with tumor malignancy, which may be a potential clinical diagnostic and prognostic marker ( Wang et al, 2009 ). Moreover, extracellular HSP90α has recently been tested as an excellent biomarker for liver and lung cancer in clinical practices ( Fu et al, 2017 ; Zhou et al, 2021 ). According to recent demonstrations, the area under the diagnosis curve of eHSP90α against lung cancers appears to be 0.857, with outstanding sensitivity and specificity.…”
Section: Introductionmentioning
confidence: 99%
“…According to recent demonstrations, the area under the diagnosis curve of eHSP90α against lung cancers appears to be 0.857, with outstanding sensitivity and specificity. Thus, eHSP90α is well anticipated to be a game-changer in tumor biomarkers for lung cancer diagnosis and prognostic assessment ( Zhou et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…6−9 Increased expression of Hsp90α is directly correlated with cancer invasiveness and severity in several cancers, implicating Hsp90α as a biomarker for cancer diagnosis. 10,11 Furthermore, high plasma levels of Hsp90α have been recognized as a clinically relevant cancer biomarker. 12,13 of Hsp90α results in the degradation of oncogenic client proteins, suggesting that the administration of Hsp90αselective inhibitors could disrupt the progression of cancers that are driven by Hsp90α-dependent substrates.…”
mentioning
confidence: 99%
“…Lithium−halogen exchange of 9 with n-butyllithium followed by the addition of 3-pentanone led to 10. An isoindoline side chain was installed Replacement of the dimethyl group in 2 with a diethyl moiety (11) led to decreased binding affinity (Table 2). Diol 14 did not manifest an improvement in binding affinity but instead exhibited a 10-fold decrease in IC 50 value.…”
mentioning
confidence: 99%
See 1 more Smart Citation